Adsorption of tetracycline hydrochloride onto ball-milled biochar: Governing factors and mechanisms. (September 2020) - Xiang, Wei; Wan, Yongshan; Zhang, Xueyang; Tan, Zhenzhen; Xia, Tongtong; Zheng, Yulin; Gao, Bin
Abstract: Pristine and ball milled wheat stalk biochars pyrolysed at 300 °C, 450 °C, 600 °C were studied for tetracycline hydrochloride (TCH) adsorption from aqueous solution. Surface characteristics of ball milled biochar (BM-biochar) were significantly enhanced over their pristine counterparts. TCH adsorption occurred largely on external surface and by filling pores of biochars as evidenced by strong positive correlation between adsorption and external specific surface area (SSA), total pore volume, or mesoporous volume. A two-stage intra-particle diffusion model, limited by the TCH diffusion through the boundary liquid layer, well described TCH adsorption. Maximum TCH adsorption occurred at about pH = 6–8. While solution cations including Na +, K + and Mg 2+ subdued TCH adsorption as they competed for adsorption sites, Ca 2+ promoted TCH adsorption due to formation of tetracycline-Ca 2+ complexes. The best performing BM-biochar was the one pyrolysed at 600 °C with TCH adsorption amount of 84.54 mg/g. Therefore, this BM-biochar has the potential for TCH removal from aqueous solutions. And the research shed light on the management of organic contaminants in real wastewater by BM-biochar. Graphical abstract: Image 1 Highlights: Ball milling enhanced external specific surface area and mesoporous volume of biochar. Ball milling increased sorption ability of biochars to TCH. TCH adsorption by BM-biochars was controlled by surface adsorption and pore filling. TCH adsorption on BM-biochars was affected by pH and cation in solution.